Keutamaan Menahan Amarah dalam Perspektif Islam: Studi Takhrij dan Syarah Hadis - Edi Susanto; Susanti Vera; Badri Khaeruman; Muhtar Gojali (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith about being alert to anger. The Prophet forbade a person to be angry with many narrations. This study uses a qualitative method through a literature study applying the takhrij hadith and syarah hadith methods through contemporary analysis. The result of this study is the discovery of the quality of the hadith about the virtue of holding anger, namely the status of authenticity according to ijma 'ulama. The conclusion of this study is the hadith of the Prophet which forbids anger in other words holding his anger will avoid the lust made by the devil because in fact anger is from the actions of the devil, guarding the hearts of others above our anger so that there is no interference between the two parties, practicing patience and fortitude heart.